Illness Causation and Folk Healing in Romblomanon Ethnomedicine among the Asi, Ini, and Onhan Peoples of Romblon, Philippines - Sherwin M. Perlas (The Bioscan, 2026)
This study documented folk beliefs concerning health and illness among the Romblomanon people belonging to the Asi, Ini, and Onhan ethnolinguistic groups in the province of Romblon, Philippines. Ethnographic and historical methods were employed, with traditional healers identified through a dragnet approach serving as key informants. Data gathering proceeded through fieldwork, manuscript preparation, validation, and final documentation. The study documented fourteen folk illnesses together with their symptoms, illness causation, diagnosis, and therapeutics. Folk illnesses were commonly attributed to supernatural beings, elemental entities, ancestral spirits, environmental exposure, bodily imbalance, food poisoning, hangin, and socially mediated encounters. Diagnostic practices included pulse-taking (himulso), ritual observation, fumigation, prayer, symbolic interpretation through tawas, and spiritual discernment. Therapeutics involved herbal medicines, massage, oracion, pig-Latin incantations, fumigation, ritual healing, and sacrificial offerings. Seven siklo ng buhay (cycle of life) works of the hilot (massage curer), three preventive rituals or health measures, lawag (remote healing), sanag (moral monies), and pathways of healer formation were likewise documented. The findings demonstrate that Romblomanon ethnomedicine remains a culturally embedded and resilient indigenous healthcare system that continues to shape local understandings of illness, wellness, and healing.